A new species of Hebrus (Hemiptera: Heteroptera: Hebridae) from Argentina - Stella, César Adrián; Pall, José Luis (Zootaxa, 2018)
The Hebridae, commonly known as “velvet water bugs,” is a small family of semiaquatic bugs (Heteroptera: Gerromorpha), distributed worldwide with approximately 220 species in 2 subfamilies and 9 genera. They are small (1.3–3.7 mm) and plump-bodied, brownish to black, and usually densely covered by setae. These predacious bugs inhabit humid terrestrial or marginal freshwater habitats. In Argentina, three species in three genera have been recorded: Hebrus engaeus Drake and Chapman, 1958, Lipogomphus lacuniferus Berg, 1879 and Merragata hebroides White, 1877. The purpose of this contribution is to describe Hebrus alvearensis sp. nov., found in the central region of Argentina, and to present a key for the species of Hebridae present in the country.